Selection of Optimum Cut-Off Grade for Surface Mining of Metalliferous Deposits: A Review - Biswas, Pritam; Sen, Phalguni (Journal of Mines, Metals and Fuels, 2017)
One of the challenging problems for surface mining operation optimization for metalliferous deposits is choosing the optimum cut-off grade while doing mine production planning, which is a very important component of mine design process. Many researchers have done significant approaches towards it but till date no full proof solution to this problem has been found. An overview on the selection of optimum cut-off grade, as suggested by various researchers has been presented in this paper.